An Investigation into Teachers’ Feedback on Learners’ Errors: Gender and Teacher Experience - Pishghadam, Reza; Kermanshahi, Paria Norouz (Richtmann Publishing, 2012)
This study seeks to scrutinize how Iranian EFL teachers correct learners; in other words, the speech act ofcorrection they employ when providing feedback on learners’ errors is examined in this study. Due to the fact thatteachers are different considering their gender and teaching experience, these two variables are taken into account in thecurrent research. To achieve this purpose, a questionnaire was distributed among 180 Iranian EFL teachers of bothgenders (male and female), with different teaching experiences (0-5, 5-10, and above 10 years). At the end, teachers’responses to each option were transformed into tables and bar graphs displaying their frequency to be analyzedafterwards. Finally, the results were discussed and some suggestions were made.